Income and Calling the Police: Examining a Nuanced Relationship Toward Theoretical Refinement - Flexon, Jamie L. (Victims & offenders, 2024)
Victims from different demographic populations are known to variably depend on police, and this appears to be the case when considering people of different income classes, an important marker of SES. The attendant research, however, is inconsistent on this point. The purpose of the current work, then, was to clarify any link between victim income and calls to the police, as well as determine any nuance belonging to a possible observed relationship. Toward this end, several theoretical frameworks were reviewed and vetted to determine which provided the most credible explanation for the findings generated using the 2019 NCVS combined with logistic regression and a marginal modeling procedure. The results revealed that victim income is associated with police calls, and that this relationship is best characterized as nonlinear. Furthermore, there are currently no theories that fully account for the results produced through this work, and consequently, an alternative explanation, the tipping point of desperation, is offered to account for the findings that can advance the strengths of existing explanations. It ends with discussion of theoretical and practical implications.